ANALISIS RELEVANSI MATA KULIAH DI PROGRAM STUDI PENDIDIKAN TEKNIK MESIN DENGAN DUNIA KERJA PARA LULUSAN - Maria Magdalena; Yuyun Estriyanto; Towip Towip (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
Current technological developments are called the industrial era 4.0 and society 5.0. Currently, education in Indonesia is experiencing an increase in the quality of higher education, namely with the issuance of the Independent Learning Campus policy which was launched by the Ministry of Education and Culture in 2020. In designing the 2021 Curriculum Study Program PTM FKIP UNS has a relationship with the needs of teacher competence, the curriculum applied in SMK, and the need for expertise competence in the industrial world. In this study, researchers will examine using a tracer study method for graduates of Mechanical Engineering Education UNS and the relevance of Mechanical Engineering Education courses at Sebelas Maret University Surakarta, especially according to alumni who graduated in 2017, 2018, 2019, and 2020. Research objectives This is "To Analyze The Relevance Of Courses In PTM With The World Of Work Of Graduates". The results of the research conducted by the author are expected to be useful as input in the Mechanical Engineering Education Study Program of FKIP UNS regarding curriculum development, both regarding aspects of planning, implementing, and evaluating curriculum. The design of this research is descriptive exploratory research which aims to describe the state of a phenomenon. In this study, it is not intended to test certain hypotheses, only to describe the existence of a variable, symptom or situation. Where the variables involved in the research will be described quantitatively (according to numerical data). The research data are alumni of graduates or graduations in 2017, 2018, 2019, and 2020. The research method used is descriptive analysis data analysis method with quantitative approach to outcome-based education exploration. The results of the study stated that the level was very high, and the irrelevant ones were approximately 10 - 11 courses or 10% of the 66 - 67 courses in mechanical engineering education. It is hoped that the Mechanical Engineering Education Study Program will increase the level of relevance of courses in synchronization with the curriculum and needs in the world of work and society in the era of the industrial revolution 4.0 and society 5.0.